The combined-disk boronic acid test as an accurate strategy for the detection of KPC carbapenemase in Central America - Zúñiga, Julio; Cruz, Gerardo; Pérez, Carlos; Microbiology Group, LCRSP; Tarajia, Musharaf (The Journal of Infection in Developing Countries, 2016)
Introduction: Carbapenemase-producing Klebsiella pneumoniae (KPC) outbreaks may cause a huge economical burden on developing countries. Furthermore, KPC can be challenging to detect. We describe the laboratory strategy for the detection of KPC from 2011 to 2013 in a tertiary care hospital in Central America with approximately 1,000 beds. Methodology: A retrospective analysis of a clinical laboratory database was done to determine the pragmatic application of the combined-disk boronic acid test during a KPC outbreak in Panama. A total of 1,026 Klebsiella pneumoniae isolates were found, of which 133 were positive for KPC. The strategy during two phases was described according to the test employed as a confirmatory test for KPC. After the K. pneumoniae isolates were detected by the VITEK 2 system, blaKPC polymerase chain reaction (PCR) and the combined-disk boronic acid test were employed as a confirmatory test during phase one. The combined-disk boronic acid test was employed as a confirmatory test for KPC during phase two. Results: The sensitivity, specificity, positive predictive value, and negative predictive value of the boronic acid test were 100%, 97%, 91%, and 100%, respectively, when blaKPC PCR was employed as a confirmatory test during the start of the outbreak. Afterwards, modified VITEK 2 system parameters resulted in 116 suspicious KPC samples and the boronic acid test confirmed 102 isolates. Conclusions: The use of an automated bacterial identification system and the boronic acid test for the detection of KPC was an effective and low-cost strategy for a clinical laboratory in Panama during an outbreak.